Sistema de verificação de integridade de dados baseado em oráculo de blockchain para internet das coisas (IoT) - Sousa, Francisco Erberto de (2023)
Society is experiencing a process of technological evolution in which some factors arise some demand attention. One of these factors is the generation of data that has been exponentially created and are present in the most environments. With the modernization of communication technologies, the Internet of Things (IoT) has gained space and consequently has been producing large-scale data. Applications can generate data of public or private interest, but a security principle that, regardless of the target audience of the IoT system, needs to be monitored is that of integrity, because the systems await complete measurement values from the sensors in order to be able to simulate their Making the right decisions. In this context, this work aims to develop a solution for the IoT scenario, capable of guaranteeing the integrity of the measured data, and based on a Blockchain oracle, which is an entity capable of guaranteeing that all data that enters the Blockchain is true. With regard to the results obtained in this work, the proposed Blockchain oracle was developed and which, in the experimental tests, reached 100% of use and allowing the conclusion that all the implemented security protocols, not only avoid the sending of data with error from to the Blockchain network, but correction methods are also applied when measurement failures are identified.